Professional Training of Future Teachers in the System of Continuous Education - Natalia Matveieva (Vasyl Stefanyk Precarpathian National University, 2017)
The author analyzes the features of training future teachers in the system of continuous education, emphasizes the need for systematic, focused, continuous improvement, and self-fulfillment. The article noted that in preparation for future professional activities in higher education are formed the basic skills and accumulated knowledge and experience that will serve as an effective teacher's growth, his creative work, the desire for further improvement. The author concludes that continuous education today serves not only the guarantee of the state and society, but also personal needs of each person.